Procedure for environmental impact assessment vs. sustainable development requirements in investment projects - Bartoszewicz, Anna; Burchart, Renata (Procedura oceny oddziaływania na środowisko wobec wymogów zrównoważonego rozwoju w projektach inwestycyjnych, 2019)
The concept of sustainable development has been supported by the European community for many years. This results in the obligation to achieve the objectives and meet the guidelines established by it for the Member States in the above scope, among others, in relation to the implementation of investment projects co-financed from EU funds. One of the most important steps in the above undertakings is the Environmental Impact Assessment which, if unreliable, may be grounds for refusing to grant funds for the investment. The purpose of this article is to indicate the key aspects of conducting an Environmental Impact Assessment (RIA) when implementing investment projects co-financed with European funds and to diagnose the factors determining the coherence of a given project with the concept of sustainable development. The considerations carried out as part of the project allowed for the identification of the determinants conditioning the coherence of a given project with the concept of sustainable development
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2019; vol. 63, nr 12, s. 7-22